PENGARUH EXPERIENTTIAL MARKETING, EMOTIONAL BRANDING DAN CITRA MEREK TERHADAP BRAND LOYALTY PADA PENGGUNA SMARTPHONE OPPO (Studi pada Mahasiswa Universitas Muhammadiyah Bengkulu) - Erika Martalena (UM. Bengkulu, 2020)
The purpose of this study was to determine the effect of Experiential Marketing, Emotional Branding and Brand Image on Brand Loyalty on Oppo Smartphone Users. This study uses a quantitative approach. Quantitative research methods are one type of research whose specifications are systematic, planned and clearly structured from the beginning to the design of the research. The population in this study is the University of Muhammadiyah Bengkulu Students and sampling using the Accidental Sampling method. Based on the results of multiple linear regression obtained by the regression equation Y = 1,341 + 0,190 (X_1) + 0.228 (X2) + 0.129 (X3) The results of the research and hypothesis show that Experiential Marketing t test results show the value of t_hit> t_ (Î± / 2) (6,139) > 1.9719) and (sig Î± = 0,000 <0.050), Emotional Branding t test results show the value of t_hit> t_ (Î± / 2) (7,934> 1.9719) and (sig Î± = 0,000 <0.050), Brand Image results of the t test show the value i.e. t_hit> t_ (Î± / 2) (3,179> 1.9719) and (sig Î± = 0.002 <0.050). Significant effect on Brand Loyalty Partially the three variables Experiential Marketing, Emotional Branding, and Brand Image have a significant influence on Brand Loyalty. Keywords: Experiential Marketing, Emotional Branding, Brand Image Brand Loyalty.